Emerging adults recall of pornography use, sexual behaviour, and sexting during childhood and adolescence - Beadsmoore, L. (2021)
This thesis contributes to the research on sexual development by exploring the age progression of the first experience of sexual activities in both same-sex and opposite-sex partners. This information is related to pornography use, sexting, attachment style and sex education.